The role of leadership style and organizational culture on employee performance - Amalina, Novita; Salsabila, Apriliani Saila; Solih, Rizal; Haryadi, Didit (Trigin Publisher, 2024)
Among effective management systems, the importance of human resources is increasing. Employee performance is an essential factor influencing success. In an organization, it is one of the most critical functions of an institution. This study aims to determine the variables that affect employee performance and develop a theoretical basis and research model. This study used associative descriptive quantitative methods with 61 respondents drawn into the sample using non-probability sampling, the sampling technique / total sampling technique, and data analysis techniques using linear regression with the help of SPSS software version 26. The results of this study show that the first hypothesis states that employee performance is influenced by leadership style. The second hypothesis states that employee performance is influenced by organizational culture. The third hypothesis, employee performance, is controlled by leadership style and corporate culture, which can simultaneously improve employee performance. This research is expected to make a theoretical contribution to the literature in this context, certainly in the context of human resource management.